(untitled) (Research, Society and Development, 2020)
This research aimed to describe the management of cancer patients during the COVID-19 pandemic. The present study is an exploratory research of the literature review type. The searches were carried out between February and April 2020, using the databases Science Direct, Lilacs and MEDLINE, with the time frame from 2014 to 2020. There was a careful selection with respect to the works used for the development of this review. The descriptors used, in an associated and isolated way, were: Oncology, coronavirus, care, prevention and COVID-19, in English, Spanish and Portuguese and indexed in DeCS. The exclusion criteria were: scientific papers with only available abstracts, duplicate publications, other methodologies, such as reflective articles, editorials, comments, letters to the editor, incomplete articles, and those that did not fit within the proposal offered for the theme and / or were outside the time frame. Theses and dissertations were used. Within the searches, 520 articles were found; however, after excluding duplicate and incomplete findings, it was restricted to 62 works, these were read individually by the researchers. At the end of the analyzes, 11 articles were used in the review. It is concluded that patients with tumors have a higher risk of COVID-19 than non-tumor patients. The remaining symptoms are similar to non-tumor patients: myalgia and fatigue. However, image manifestations are more serious and more serious complications are more likely. The older you are, the greater the risk of serious clinical events and the worse the prognosis.